Case Report: A Case Series of Immunobiological Therapy (Anti-TNF-α) for Patients With Erythema Nodosum Leprosum - Mendes, Ana Flávia Moura; Gomes, Ciro Martins; Kurizky, Patrícia Shu; Ianhez, Mayra (Frontiers in Medicine, 2022)
Patients with leprosy may experience a chronic and severe type II leprosy reaction (erythema nodosum leprosum, ENL) that may not respond to thalidomide and systemic immunosuppressants or may even cause serious adverse events. We here present four patients in whom anti-TNF-α therapy was used with successful results and compare our findings with other published cases. Four patients with chronic and severe ENL who did not respond to, at least, thalidomide and steroids (high doses) were followed up at two reference centers in Brazil. A thorough laboratory investigation was performed to exclude tuberculosis and other diseases before the start of immunobiological medication. Three patients were started on etanercept, and one patient was started on adalimumab. Of all patients, three developed severe adverse events resulting from the use of classical immunosuppressants for ENL (cataracts, deep vein thrombosis, diabetes, and osteoporosis). In all cases, a reduction in the number of ENL and, at least half of the immunosuppressant dose between 6 months and 2 years, were observed. Long-term follow-up of one patient revealed a dramatic reduction in hospital admissions due to ENL, from 12 instances in one year (before biologic therapy) to none (after biologic therapy), along with an improvement in condyloma acuminatum. In addition, no adverse events were observed with biologics. Treatment with anti-TNF-α therapy may be used as an alternative in patients with chronic and severe ENL who do not respond to traditional treatment (e.g., thalidomide, steroids, and other immunosuppressants). This treatment can help reduce the frequency of ENL, the immunosuppressive burden, and the number of hospital admissions.